In vitro culture of olfactory epithelial cells from Megalobrama amblycephala and their response to amino acid mixtures and prostaglandin F2α - Guan, Suhua; Huang, Xin; Zhu, Dongmei; Gao, Zexia; Liu, Han (Frontiers in Cell and Developmental Biology, 2025)
Olfaction is essential for the survival and reproduction of fish, as it facilitates foraging, food localization, mate selection, and breeding. The in vitro cultured olfactory epithelial cells will provide an important resource for research on how fish use olfaction to detect odor molecules in their environment. In this study, olfactory epithelial cells from Megalobrama amblycephala were cultured in vitro to investigate their responses to various odors, amino acids, and prostaglandin F2α (PGF2α). Initially, the olfactory epithelial cells were cultured in vitro using the explant method and collagenase digestion technique. Based on observations of in vitro growth characteristics, collagenase digestion demonstrated superior growth stability and morphological features of ciliated neurons. The presence of olfactory neurospheres was identified through scanning electron microscopy (SEM). Immunofluorescence analysis revealed that most of the cells cultured were labeled with NEUN antibody. Additionally, the expression of olfactory receptors (ORs) was detected in the in vitro cultured olfactory epithelial cells using fluorescence in situ hybridization (FISH) and reverse transcription PCR (RT-PCR). Stimulation with amino acids mixture and PGF2α significantly increased the number of olfactory epithelial cells labeled with pERK. RNA-seq analysis revealed that 1,276 differentially expressed genes (DEGs) were identified following PGF2α stimulation, with pathways related to olfaction and reproduction being significantly enriched. Collectively, this study successfully established an in vitro model of the olfactory epithelium cells in M. amblycephala and preliminarily investigated its response to odorant molecules, providing a valuable platform for research on fish olfactory function.